The Effect Of Exclusive Breastfeeding Education Through Telehealth With The Sociodrama Method Towards Knowledge Of Post Partum Mother - Siti Nur Endah Hendayani; Siti Nur Azizah; Rika Nur Hasanah (Science Midwifery, 2022)
Breast milk is the primary source of nutrition for newborns and toodler, containing fat, protein, carbohydrates and variable minerals and vitamins. Breast milk also contains substances that help protect an infant against infection and inflammation, whilst also contributing to healthy development of the immune system and gut microbiome. Effort for increase exclusive breastfeeding among mother is increase of mother knowledge through education. Utilization of the sociodrama method in education will make it easy delivery message to mother. The aim of this study is to identified the effect of exclusive breastfeeding education through telehealth with the sociodrama method towards knowledge of post partum mother. This study uses a quasi-experimental design with one group pretest-posttest. The population in this study were postpartum mothers, sampling was taken a total sampling of 31 postpartum mothers who were in the working area of ​​the Cibeber Health Community Center at Cimahi City. The primary data collection technique used was a questionnaire with a sociodrama video intervention. Data analyzed by paired t test non parametic wilcoxon at a significant level of 5%. The conclusion of this study shows that there is an effect of providing exclusive breastfeeding education through telehealth with the sociodrama method on mother's knowledge. The recommendation based on the results of this study is that health workers use the sociodrama method as an alternative media in providing education to breastfeeding mothers